2011
DOI: 10.1007/s00062-011-0057-6
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Angioplasty and Stenting Without Protection Devices

Abstract: Carotid stent placement without the use of distal protection devices was found to be a safe and effective procedure with a relatively low incidence of periprocedural complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…CAS ile ilgili yapılan çalışmalarda genelde proksimal yada distal korumanın yapıldığı izlenmiştir. Bizim hastalarımızda ise proksimal ya da distal koruma yapılmamasına rağmen sadece bir hastada 24 saatten kısa süren nörolojik fonksiyon bozukluğu gözlenmiştir (27).…”
Section: Gereç Ve Yöntemunclassified
“…CAS ile ilgili yapılan çalışmalarda genelde proksimal yada distal korumanın yapıldığı izlenmiştir. Bizim hastalarımızda ise proksimal ya da distal koruma yapılmamasına rağmen sadece bir hastada 24 saatten kısa süren nörolojik fonksiyon bozukluğu gözlenmiştir (27).…”
Section: Gereç Ve Yöntemunclassified
“…Many reviews and meta-analyses showed that the rate of ipsilateral stroke and death was less in patients treated with CAS and protection devices [3,4]. On the other hand, several uncontrolled studies showed fantastic results in patients treated without the use of protection devices [5][6][7][8][9]. In a recent meta-analysis, the usage of CPD reduced the rate of symptomatic stroke after CAS; however, in patients with symptomatic lesions, its efficacy was not much obvious and therefore, its routine usage during the procedure should be assessed well before mandatory usage [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, there is no evidence in the recently published literature supporting the superiority of either of these techniques. Standard poststent balloon angioplasty has become the standard of care in many vascular centers, [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and only some interventionalists 19, [36][37][38][39][40][41] prefer performing poststent angioplasty on a selective base. On the basis of the latter studies, standard poststent balloon angioplasty may be associated with additional risks in patients with acceptable angiographic results, without additional post-carotid artery stent placement (CAS) angioplasty.…”
mentioning
confidence: 99%